PENGARUH PENGGUNAAN MEDIA INTERAKTIF TERHADAP KETERAMPILAN MEMBACA SISWA KELAS IV - Wiwin Agus Salim; Muh. Taufiq; Hadiatul Rodiyah; Arif Rahman Hakim (Universitas Islam Sultan Agung, 2026)
The low reading skills of fourth-grade students at SD Islam Tahfizh Kerongkong are influenced by the lack of use of interactive media in the teaching and learning process. This condition has an impact on declining students' interest and learning outcomes in Indonesian. This study aims to determine the effect of interactive media use on the reading skills of fourth-grade students at SD Islam Tahfizh Kerongkong in 2025. This type of research used a quantitative research design with a pre-experimental one-group pretest-posttest design. The sampling technique used was saturated sampling with a total of 20 students. The research instrument was a reading skills test administered at the pretest and posttest stages. Based on the results of the normality test, the data were normally distributed. The pretest results showed an average score of 43.70, while the posttest results increased with an average score of 85.25. Based on the results of the hypothesis test using the t-test, the calculated t-value > t-table was 12.25 > 1.729 at a significance level of 0.05 with db = N-1 = 19. Thus, Ho is rejected and Ha is accepted. The results of this study indicate that the use of interactive media has a significant effect on improving the reading skills of fourth-grade students at SD Islam Tahfizh Kerongkong.